Heavy metals in some tissues and organs of Capoeta capoeta umbla (Heckel, 1843) fish species in relation to body size, age, sex and seasons - Canpolat, O; Çalta, M (Parlar Scientific Publications (P S P), 2003)
In the present study heavy metals in some tissues and organs of Capoeta capoeta umbla fish species from Keban Dam Lake Elazig (Turkey) in relation to body size (lenght and weight), sex, age and seasons were determined. Only Cu, Fe, Mn and Zn were detected in the tissues and organs examined. In general, the lowest levels of these metals were found in muscle and skin compared with other tissues and organs. The changes of heavy metal levels in tissues and organs were discussed in relation to size, sex, age of fish and seasons in which fish samples were collected.
Keywords: heavy metals; Capoeta capoeta umbla; body size; seasons; Hazar Lake; Turkey